Unintended Consequences of Scaling Social Impact Through Ecosystem Growth Strategy in Social Enterprise and Social Entrepreneurship - Islam, SM (Elsevier BV, 2020)
Scaling social impact is regarded as the main currency in social enterprise and social entrepreneurship. Many social enterprises scale their social impact through ecosystem growth strategy, under which they indirectly address targeted social problems by growing and/or sustaining a supportive social enterprise ecosystem through activities such as organising advocacy campaigns and supporting other social enterprises to grow. However, the existing literature is largely biased towards the success stories of ecosystem growth strategy. Countering this “success bias”, this article presents a framework describing how, under certain conditions, scaling social impact through ecosystem growth strategy can create unintended consequences. In doing so, this paper also challenges the prevailing reductionist view of ecosystem growth as a social impact scaling strategy and provides a more reliable and comprehensive account of this scaling strategy. This article hopes to stimulate future research on greater understanding and management of unintended consequences of ecosystem growth strategy in social enterprise, as well as delineating the boundary conditions of this strategy with regard to scaling social impact.
Keywords: Social enterprise; Scaling social impact; Ecosystem growth strategy; Unintended consequence; Social entrepreneurship